The Legal Nature of Smart Contracts Programmed using Blockchain Technology - Younis Okleh Muflih Almahasneh (International Journal of Law Research and Studies, 2024)
The advent of blockchain technology has given rise to a new form of digital agreement known as smart contracts, which are self-executing contracts with the terms of the agreement written directly into code. This paper explores the legal landscape surrounding smart contracts and their unique characteristics in the context of traditional contract law. With the proliferation of blockchain technology, the legal implications of smart contracts have become a topic of increasing interest to legal practitioners, businesses, and policymakers. The paper addresses key aspects such as enforceability, validity, and potential liabilities. The paper addresses the challenges and opportunities presented by smart contracts, aiming to provide clarity and guidance to stakeholders working in this rapidly evolving field. By analyzing case law, regulatory frameworks, and industry practices, this paper seeks to shed light on the legal complexities associated with smart contracts programmed using blockchain technology. A key focus of this research is the enforceability of smart contracts under existing legal frameworks. This includes examining contractual intent, offer and acceptance, consideration, and capacity, and how these traditional contract law principles translate into the world of smart contracts. Furthermore, the paper delves into the potential legal liabilities and dispute resolution mechanisms associated with smart contracts, and provides insights into the evolving landscape of contractual relationships facilitated by blockchain technology. The findings of this research have significant implications for legal practitioners and businesses operating in industries where smart contracts are used. The paper makes recommendations for legislative clarity, standardization of smart contract protocols, risk assessment, regulatory compliance, dispute resolution mechanisms, education and awareness, interdisciplinary collaboration, and the need for ongoing monitoring and adaptation. These recommendations aim to contribute to the ongoing discourse and proactive adaptation of the legal nature of smart contracts, and to foster an environment that balances innovation, legal certainty, and protection.
Keywords: Smart Contracts; Programmatic Contracts; Blockchain Technology; Law